Double‐balloon endoscopy for duodenal diverticulitis with calculus after intestinal reconstruction: A case report - Kai Toyoshima; Yunosuke Takishin; Kiko Toda; Katsuma Nakajima; Yutaro Otuka; Daisuke Yokoyama; Tetsuhito Muranaka; Yasuyuki Kunieda (DEN Open)
Abstract Small‐bowel diverticulosis is relatively common, but there is no set treatment strategy for duodenal diverticulitis with stone impaction. A woman aged in her 70s presented with a chief complaint of abdominal pain, and she had been reconstructed by the Roux‐en‐Y method after total gastrectomy. We performed an enhanced computed tomography which revealed edematous wall thickening of the duodenum. We diagnosed her with duodenal diverticulitis and treated them with antibiotics but her disease was not cured, we therefore attempted endoscopic stone removal as a nonoperative treatment. After stone removal with a nonoperative procedure, when we contrasted the duodenal papillary diverticulum, it was found to form a fistula on the other side, and the successful treatment made her discharged on the 17th day. The duodenal diverticulitis with calculus is extremely rare, and there is no report to treat it using double‐balloon endoscopy, therefore we report this case with a literature review.